Incidence and Risk Factors for Acute and Persistent Postoperative Pediatric Pain: The 4P Prospective Observational Multicenter Study - Johanna Broman; Niklas Nielsen; Anna K. M. Persson (Journal of Personalized Medicine, 2026)
Background: Large prospective studies on the prevalence of acute and persistent pain in children are limited, and risk factors associated with post-surgical pain in children remain unclear. Objective: To examine the incidence of pediatric acute (APOP) and persistent postoperative pain (PPOP) and to determine whether factors such as age, sex, preoperative anxiety/sleep disturbance, preoperative pain and parental stress are associated with increased risk. Design: Prospective observational multicenter study. Setting: Hospitals performing pediatric surgery in southern Sweden. Patients: 601 children aged 1–17 years planned for one of the European Society of Pediatric Anesthesia (ESPA) pre-defined surgical procedures: inguinal hernia, circumcision/hypospadias/retentio testis, adenoidectomy/tonsillectomy/tonsillotomy, appendectomy and orthopedic acute fracture surgery. Main outcome measures: Postoperative pain in PACU after 24 h and 3, 6 and 12 months, level and description of the pain and effect on the child. Results: The incidence of APOP in the postoperative care unit was 0–27%, increasing to 13–58% after 24 h depending on surgery type. The incidences of PPOP were 4–24%, 4–30%, and 0–19% at 3, 6, and 12 months, respectively, depending on surgery type. Older age was a risk factor for APOPPACU (OR 1.2, p < 0.001) and APOP24h (OR 1.3, p < 0.001), whereas female sex was a risk factor only for PPOP6months (OR 2.1, p = 0.028). Self-reported parental stress was a significant risk factor for postoperative pain at all follow-ups, exhibiting increasing influence (APOP24h OR 1.2, p = 0.001; 3months OR 1.5, p < 0.001; 6months OR 1.3, p < 0.001; 12months OR 1.5, p < 0.001). Preoperative anxiety/sleep disturbance only affected APOPPACU (OR 2.0, p = 0.008), whereas preoperative pain was not a risk factor. Conclusions: The incidences of APOP and PPOP were lower than in previous studies. Possible risk factors for acute pain include older age and preoperative anxiety/sleep disturbance. Only self-reported parental stress was a consistent risk factor for persistent pain.